Automatic text searching for information retrieval - Salton, Gerald (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
The capabilities of automatic text search systems are reviewed and evaluation results are cited comparing the performance of automatic text searching systems with the effectiveness of manual controlled-term indexing methods. Some possibilities are then examined for improving automatic text search systems, including the use of complex content identifiers instead of single words, and the introduction of user-system interaction. A likely scenario is given for the operations of future automatic text search systems.